How to draw vampires - Butkus, Mike; Chea-Butkus, Davin; Destefano, Merrie 1954- (Irvine, CA Walter Foster, 2010)
Discover the folklore and history of vampires, and learn how they were transformed from a ghoulish demon into a romantic charmer. Discover how to capture the vampire in pencil, acrylic and oil, and create your own undead beast
Vampire basics -- Drawing vampires -- Painting vampires -- Vampires & digital illustration
"Discover the secrets to drawing, painting, and illustrating immortals of the night."--Cover
Keywords: Drawing -- Technique; Vampires in art